Designing Board Games: A Practical Guide for Educator to Teach Computer and Basic Network in Class - Ayu Indah Wulandari; Dwi Maryono; Basori Basori (Journal of Informatics and Vocational Education, 2023)
Board Games can be a highly engaging and motivating resource to support Computer and Basic Network teaching in class. However, the development of board games to facilitate the communication of the subject may not be an easy task for those with no prior experience in designing games. For instance, the various classification of educational game features, construction of the game mechanism, and lack of scholarly guidance for designing and their efficacy in formal learning may hinder the game development process. To address this issue, this study presents a hands-on game development framework for teachers and researchers on how to design educational games. The framework is divided into five that build upon each other to create a student-centered educational resource as well as provide a means of evaluation.